Methods of reliability multivariate analysis - Polenova N. A. (Priority directions of scienceand education development, 2016)
this article deals with the computer-aided analysis of electronic tools reliability taking into account the redundancy in Microsoft Excel environment, the reliability calculation is implemented with an expanded set of correction factors for the selected backup version with the formation of the working database of backup options.
Keywords: база данных; надежность; reliability; многовариантный анализ; интенсивность отказов; вероятность безотказной работы; database; multivariate analysis; failure rate; the probability of failure-free operation